2014
DOI: 10.1364/oe.22.014004
|View full text |Cite
|
Sign up to set email alerts
|

Coupled-resonator optical waveguides for temporal integration of optical signals

Abstract: In this paper, we propose and numerically investigate an all-optical temporal integrator based on a photonic crystal cavity. We show that an array of photonic crystal cavities enables high-order temporal integration. The effect of the value of the cavity's free spectral range on the accuracy of the integration is considered. The influence of the coupling coefficients in the resonator array on the integration accuracy is demonstrated. A compact integrator based on a photonic crystal nanobeam cavity is designed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…It was shown that such gratings have a high efficiency and can significantly reduce the size of the projection devices used in mobile phones, etc. Modern computational and technological capabilities allow colleagues and students of I. N. Sissakian to transfer from the tasks of diffractive optics to the problems of diffractive nanophotonics [122][123][124][125][126][127][128][129][130][131].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that such gratings have a high efficiency and can significantly reduce the size of the projection devices used in mobile phones, etc. Modern computational and technological capabilities allow colleagues and students of I. N. Sissakian to transfer from the tasks of diffractive optics to the problems of diffractive nanophotonics [122][123][124][125][126][127][128][129][130][131].…”
Section: Resultsmentioning
confidence: 99%
“…These results open up the prospects of solving one of the main tasks of computer optics -implementation of optical calculations [124][125][126][127] and lay the intellectual foundations of advanced information technologies [131]. Finally, we mention two practical applications of computer optics elements: protective holograms [132][133] and optical filters for professional and amateur photography [134] …”
Section: Resultsmentioning
confidence: 99%
“…Using the "backlog" -developed at the Image Processing Systems Institute of the RAS (IIPS RAS), for use in the field of optical instrument engineering [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] and diffraction nanophotonic [65][66][67][68][69][70][71][72][73][74] -for the designing of diffraction acoustic elements with certain characteristics would seem to be a very promising direction for future work. …”
Section: Resultsmentioning
confidence: 99%
“…We use this methods not only for the study of diffractive optical elements (in particular, of short-focus DOEs), but also for the study of nanophotonics components [66][67][68][69][70][71][72][73][74], for the design of equipment for hyperspectral remote sensing [75][76][77][78][79] and solving other urgent tasks of diffractive nanophotonics [80]. …”
Section: Resultsmentioning
confidence: 99%